12 Isolated but not alone: critical care communication in the time of covid-19. (16th November 2020) - Baker, Laura; Lindsay, Helène; Payton-Crisp, Claire; Robinson, Kath
Abstract : Many communication challenges became evident when the coronavirus pandemic led to the closure of Critical Care Units to visitors. Extra staff drafted in were unfamiliar with the ICU environment and needed to focus on direct patient care. The increased ICU footprint meant calls might be misdirected. Personal protective equipment (PPE) hampered hearing, speaking and phone use. Staff were unable to hold face-to-face family meetings and families were unable to be at the bedside which would, in normal times, enable them to be part of the patient's hospital journey. Inevitably, this all led to an increased volume of phone calls. To try to solve some of these issues, it was decided that a dedicated team was needed to establish open lines of communication between patient, family and staff. A group of senior nurses from across the hospital were brought together to form the Critical Care Family Liaison Team (FLT). FLT now give coordinated information and are the first point of contact for families. Interventions include using technology such as FaceTime and Zoom to allow 'virtual visiting', conference calling for family updates, bedside photographs, voice recordings sent in by families and music playlists. The role for the FLT has evolved; the team was set up rapidly at the start of lockdown and members were in their new roles within a week. Daily verbal feedback was gathered from the medical team and interventions changed as necessary. It is difficult to assess what the situation would have been without this innovation. Formal feedback was requested from all staff members working in Critical Care and from patients and their families. Qualitative and 5 point likert scale responses have been positive. Further data collection and feedback is ongoing to ensure the service continues to evolve as we move towards a new normal.